A Historical Perspective on the Essex-Lopresti Injury - McGlinn, Evan P. (2013)
An Essex-Lopresti injury is a fracture of the radial head with concomitant dislocation of the distal radioulnar joint and rupture of the interosseous membrane. Poor outcomes have been associated with this rare injury if the dislocation of the distal radioulnar joint is missed in the acute setting. This injury is named after the British orthopedic surgeon Peter Essex-Lopresti, who made a number of important observations about this injury in 1951. Peter Essex-Lopresti was a promising young surgeon, and his untimely death at the age of 35 brought an early end to a remarkable career. This article investigates the evolution of treatment for this injury and sheds light on the life of the surgeon for whom the injury is named.